A study on the slum clearance redevelopment project and the community design project for disaster in Koto-delta - Fujisaki, Motoki; Reyes, Joseph Thomas; Toyokawa, Saikaku (International Planning History Society Proceedings, 2018)
The paper puts it focus on the activities of university researchers to organize the top-down urban planning and bottom-up community design with the theme of disaster in Koto-delta. Moreover, comparative and analysis of statistical data of Koto-delta for half a century show the necessary conditions for considering the disaster prevention planning. Koto-delta is the most dangerous area for disaster in Tokyo. Takayama presented the Koto Cross Disaster Prevention Belt Conception, after studying his laboratory, became the foundation of the current planning. While disaster prevention bases and public facilities have increased the disaster prevention performance of the area, the aging and unused facilities are now a problem. Otani and Sato aimed to improve the community by cooperative rebuilding of residents, but the discussion was difficult, and maintenance did not proceed. The statistical data shows that the safety of the area improved, but in addition to the failure of social mix due to largescale development, the loss of regional landscape and diversity due to the promotion of detached rebuilding, the resilience is decreasing.